Transcriptomic Profiling Reveals a Role for TREM-1 Activation in Enterovirus D68 Infection-Induced Proinflammatory Responses - Li, Jinyu; Yang, Shan; Liu, Sihua; Chen, Yulu; Liu, Hongyun; Su, Yazhi; Liu, Ruicun; Cui, Yujun; Song, Yajun; Teng, Yue; Wang, Tao (Frontiers in Immunology, 2021)
Increasing cases related to the pathogenicity of Enterovirus D68 (EV-D68) have made it a growing worldwide public health concern, especially due to increased severe respiratory illness and acute flaccid myelitis (AFM) in children. There are currently no vaccines or medicines to prevent or treat EV-D68 infections. Herein, we performed genome-wide transcriptional profiling of EV-D68-infected human rhabdomyosarcoma (RD) cells to investigate host-pathogen interplay. RNA sequencing and subsequent experiments revealed that EV-D68 infection induced a profound transcriptional dysregulation of host genes, causing significantly elevated inflammatory responses and altered antiviral immune responses. In particular, triggering receptor expressed on myeloid cells 1 (TREM-1) is involved in highly activated TREM-1 signaling processes, acting as an important mediator in EV-D68 infection, and it is related to upregulation of interleukin 8 (IL-8), IL-6, IL-12p70, IL-1β, and tumor necrosis factor alpha (TNF-α). Further results demonstrated that NF-κB p65 was essential for EV-D68-induced TREM-1 upregulation. Moreover, inhibition of the TREM1 signaling pathway by the specific inhibitor LP17 dampened activation of the p38 mitogen-activated protein kinase (MAPK) signaling cascade, suggesting that TREM-1 mainly transmits activation signals to phosphorylate p38 MAPK. Interestingly, treatment with LP17 to inhibit TREM-1 inhibited viral replication and infection. These findings imply the pathogenic mechanisms of EV-D68 and provide critical insight into therapeutic intervention in enterovirus diseases.